Peningkatan Kapasitas Siswa SMA Institut Indonesia tentang Penulisan Ilmiah Bertemakan Green Building - Purwanti, Hani; Firmawan, Ferry; Masvika, Hendra; Purwanto (Faculty of Engineering, Universitas Semarang, 2026)
The increasing human activities and climate change have significantly contributed to global warming, which threatens environmental sustainability. The construction sector is one of the major contributors to environmental degradation and climate change due to its high carbon emissions. As a solution, the implementation of the green building concept has been developed. This concept emphasizes the use of renewable energy and the application of zero-energy-use principles. This condition creates opportunities for students of SMA Institut Indonesia Semarang to produce scientific articles and academic writings related to green building. This activity aims to improve students’ abilities in writing scientific articles on green building themes that align with environmental and sustainability issues. The methods applied include lectures, discussions, and simulations. The pre-test and post-test results indicate an increase in participants’ understanding from 43.75% to 81.25% regarding green building concepts and scientific writing. This improvement serves as an indicator of the program’s success. The activity received positive responses and full support from the school, and it had a beneficial impact on enhancing students’ fundamental understanding of scientific writing, particularly in the green building topics that are highly relevant to current environmental issues.